Perceived Organizational Support in Education: A Systematic Literature Review and Implications for School Management and Leadership - Hanyfa Shofia Azahra Zulfa; Eka Prihatin; Abubakar Abubakar; Hanyfa Shofia Azahra Zulfa; Eka Prihatin; Abubakar (Universitas Negeri Malang, 2026)
Perceived organizational support (POS) has attracted increasing attention in educational research, yet existing evidence remains theoretically fragmented and offers limited guidance for school management and leadership. This study aims to synthesize the literature on teachers’ POS by mapping teacher outcomes, dominant theoretical frameworks, leadership and organizational antecedents, and their implications for educational leadership. Following the PRISMA 2020 guidelines, 89 empirical studies published between 2019-2026 were identified through Scopus and ERIC and synthesized narratively. The findings: work engagement, teacher well-being, job satisfaction, and teacher performance are the most prominent promotive outcomes, whereas burnout and turnover intention represent the primary protective outcomes. Social Exchange Theory dominates the literature, alongside Organizational Support Theory, the Job Demands–Resources model, Conservation of Resources Theory, and Self-Determination Theory. The review further suggests that POS operates through both promotive and protective mechanisms and functions not only as a direct predictor but also as a mediator and moderator of teacher outcomes. For school management and leadership, POS should be understood as a system-level organizational outcome shaped by the alignment of leadership practices, organizational procedures, and material working conditions. Future research should adopt more longitudinal, mixed-methods, and cross-cultural designs, particularly in underrepresented contexts such as Islamic educational institutions.